Is mobile app a new political discussion platform? An empirical study of the effect of WeChat use on college students' political discussion and political efficacy. - Hua Pang (PLoS ONE, 2018)
In the last couple of years, the increasing application and popularization of mobile app have dramatically transformed people's daily political lives through offering innovative mechanisms for interpersonal communication. While a majority of past studies on WeChat have mainly focused on its characteristics, only few documents have unearthed the potential effect of using such emerging social media on facilitating political discussion and increasing political efficacy. Given those, this study adopted uses and gratifications approach to explore the possible relationships between gratifications-sought, the intensity of WeChat usage on mobile phones, online political discussion, and political efficacy among college students in China. An empirical survey with 282 WeChat users reveals that WeChat as a relatively new outlet of political information, which fosters online political discussion with others about government and politics. Contrary to the expectation, the intensity of WeChat usages is not helped to strengthen or enhance individual's level of internal or external political efficacy. Furthermore, hierarchical regression analyses demonstrate that information needs and recognition needs are positive predictors of internal political efficacy. Overall, these obtained findings may shed more up-to-date insights on the meaningful role of the mobile-based communication technology in promoting citizens' democratic engagement in a developing country.